2022
DOI: 10.18203/2349-2902.isj20220326
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of total leucocytes count, C-reactive protein and total bilirubin in acute appendicitis: a prospective study

Abstract: Background: The diagnostic like history, clinical examination and prejudiced role of white cell count and C-reactive protein (CRP) in acute appendicitis has been studied widely but still remains controversial. Therefore, the purpose of this study was to evaluate the diagnostic value of CRP, Total leucocytes count, bilirubin levels individually in cases of acute appendicitis and its complications. Methods: This randomized prospective study was conducted in department of Surgery and our surgical hospital, Palanp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…It is usually observed that a lot of patients who undergo an emergency appendectomy are proven to be negative based on histopathological findings (Gold standard for diagnosing appendicitis) 15 . Despite many advances in medical science, a negative appendectomy rate of 15-25% 16 and perforation rate of 25.8% 17 showing the sensitivity of serum Bilirubin in acute appendicitis as 65% and a specificity of 70% 18 . Birkan Birben also conducted a study on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…It is usually observed that a lot of patients who undergo an emergency appendectomy are proven to be negative based on histopathological findings (Gold standard for diagnosing appendicitis) 15 . Despite many advances in medical science, a negative appendectomy rate of 15-25% 16 and perforation rate of 25.8% 17 showing the sensitivity of serum Bilirubin in acute appendicitis as 65% and a specificity of 70% 18 . Birkan Birben also conducted a study on this topic.…”
Section: Discussionmentioning
confidence: 99%